2023
DOI: 10.1007/s00227-023-04205-4
|View full text |Cite
|
Sign up to set email alerts
|

Extending deep-sea benthic biodiversity inventories with environmental DNA metabarcoding

Abstract: Inventories of biodiversity are crucial for helping support conservation and management efforts, yet the deep-sea, which is the largest biome on earth remains vastly understudied. Recent advances in molecular detection methods offer alternative techniques for studying inaccessible ecosystems, including those at depth. In this study we utilized environmental DNA metabarcoding, a first for studying deep-sea benthic environments in southern Africa, to assess biological diversity and to test the effects of depth a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 62 publications
1
0
0
Order By: Relevance
“…In addition, two phyla of Gastrotricha and Hemichordata were exclusively found at two stations (P30 and P112) characterized by the shallowest water depth, suggesting their distribution patterns are likely influenced by depth gradients. These results indicated that the alpha diversity declines with the increasing water depth in the studied TAB system, supporting previous findings that depth gradients restricted the distributions of various metazoan taxa in deep seafloor (Brandt et al, 2020;Liu et al, 2022;Oosthuizen et al, 2023).…”
Section: The Characteristics Of Diversity and Taxa Distribution In A ...supporting
confidence: 90%
“…In addition, two phyla of Gastrotricha and Hemichordata were exclusively found at two stations (P30 and P112) characterized by the shallowest water depth, suggesting their distribution patterns are likely influenced by depth gradients. These results indicated that the alpha diversity declines with the increasing water depth in the studied TAB system, supporting previous findings that depth gradients restricted the distributions of various metazoan taxa in deep seafloor (Brandt et al, 2020;Liu et al, 2022;Oosthuizen et al, 2023).…”
Section: The Characteristics Of Diversity and Taxa Distribution In A ...supporting
confidence: 90%